Cost‐Effectiveness Analysis of Surgical Strategies Versus Medical Management for Rheumatic Heart Disease in Rwanda - Vongai Mlambo; Songnan Wang; Maurice Musoni; Hannah Rando; Lambert Ingabire; Ceeya Patton‐Bolman; Gloria Mukeshimana; Evariste Ntaganda; Ralph Bolman; Eran Bendavid; Yihan Lin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background One‐third of the global rheumatic heart disease burden lies in sub‐Saharan Africa, where 17% of patients with severe rheumatic heart disease die within 3 years without valve surgery. Surgery is often considered uneconomical, although this assumption is not grounded in cost‐effectiveness analyses. Methods We evaluated the cost‐effectiveness of mechanical valve replacement, bioprosthetic valve replacement, and valve repair compared with medical management for patients with severe rheumatic heart disease in Rwanda. Using a Markov model, we simulated disease progression, incorporating transition probabilities from a meta‐analysis of regional observational studies. Costs were calculated using microcosting, and health effects were measured in disability‐adjusted life‐years (DALYs). Cost‐effectiveness was defined by a willingness‐to‐pay threshold of United States dollars (USD) $2307 per DALY, which is 3 times Rwanda's gross domestic product per capita. A 3% discount rate for costs and DALYs was applied. Results Surgical strategies extended life expectancy from 7 to 11 to 13 years. Mechanical and bioprosthetic valve replacements were cost‐effective compared with medical management. Mechanical valve replacement was most efficient, averting 5.64 discounted DALYs for a lifetime discounted cost of USD $10 539.34, with an incremental cost‐effectiveness ratio of USD $1704 per DALY. Bioprosthetic valve replacement averted 5.27 discounted DALYs but incurred higher costs (USD $10 873.06). Valve repair only averted 3.30 DALYs despite being least expensive (USD $8790.19). Repair became the most efficient surgical strategy if valve degeneration rates dropped <3.7% annually. Conclusions Mechanical valve replacement is the most efficient surgical strategy for severe rheumatic heart disease in sub‐Saharan Africa, challenging assumptions that surgery is uneconomical. Reducing surgery costs and optimizing anticoagulation could further enhance cost‐effectiveness.